Pharmacological insights and therapeutic advances of mangiferin against various pathological conditions in liver diseases - Tanvir Zaman Shoyshob; Sumaya Akter; Muhammad Ramiz Uddin; Mithila Farjana; Akhi Moni; Wonhyo Seo; Md. Golzar Hossain; Md Jamal Uddin (Journal of Advanced Biotechnology and Experimental Therapeutics)
Currently, liver diseases have become a serious global health issue, and this situation occurs due to the exposure of the liver to different agents, such as chemicals, alcohol, viruses, and autoimmune diseases. Mangiferin is a natural bioactive xanthone C-glycoside compound and a potent antioxidant that is widely found in medicinal plants such as the leaves of Mangifera indica L. (Anacardiaceae). It possesses a wide range of biological properties, such as antidiabetic, hepatoprotective, anti-inflammatory, antioxidant, and anticarcinogenic activities. The purpose of this literature review was to delineate the hepatoprotective effects of mangiferin, a natural bioactive compound without side effects, and explain how it protects the liver via the suppression of pathological conditions involved in liver diseases. Relevant published research articles from peer-reviewed journals were searched in PubMed and Google Scholar to gain insights into the consequences of mangiferin in liver diseases. Several studies have suggested that pretreatment with mangiferin decreases hepatic inflammation, oxidative stress, apoptosis, fibrosis, endoplasmic reticulum (ER) stress, and hepatic dysfunction and concomitantly ameliorates the morphological structures of the liver. Therefore, mangiferin could be considered a multitarget therapeutic and promising drug candidate for the treatment of hepatic diseases, although a detailed mechanistic explanation needs to be provided. This literature review highlights the pathological conditions (inflammation, oxidative stress, apoptosis, ER stress) associated with liver diseases as well as the hepatoprotective and therapeutic effects of mangiferin in the liver. [ J Adv Biotechnol Exp Ther 2025; 8(1.000): 125-138]